ANALISIS KEMAMPUAN KOGNITIF SISWA MENYELESAIKAN MASALAH KONTEKSTUAL MATERI PELUANG - Marianus Ardin Suryanto; Natalia Peni; Konstantinus Denny Pareira Meke (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2024)
This research aims to determine students' cognitive abilities in solving contextual problems in class VIIIA mathematics learning at SMPS Kristen Ende on opportunity material. The type of research used is descriptive with a qualitative approach. The population in this study were all students in class VIII at SMPS Kristen Ende and the sample in this study was class VIIIA, totaling 25 students. Data collection techniques use written tests and interviews. The results of this research show that the ability of class VIA students at SMPS Kristen Ende to solve contextual problems with opportunity material is at the cognitive level, remembering at 85%, including the high category, understanding at 79% including the high category, applying at 76 % is in the medium category, analyze is 94% is in the high category, evaluate is 23% is in the low category, and create is 69% is in the low category. The results of research conducted on 25 students taken as samples showed that 7 students or 28% had high cognitive abilities, 13 students, or 52% had medium cognitive abilities, and 13 students, or 52% had cognitive abilities in the low category. 5 students or 20%.